Integration of Audio-Visual Aids in English Language Teaching: Challenges and Prospects - M. Arshiya, Ph. D,Dr. G.J. Hamlin (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The increasing use of audio-visual aids has reshaped English Language Teaching(ELT) by offering learners authentic input and contextual meaning